Faktor-Faktor yang Memengaruhi Produksi Manggis (Garcinia Mangostana) Di Desa Puspahiang Kecamatan Puspahiang Kabupaten Tasikmalaya - Reva Noormahesa; Candra Nuraini; Unang Unang (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2024)
Mangosteen is one of the prospective horticultural commodities in Indonesia. It is a perennial plant with a lifespan of several decades. On average, mangosteen trees in Indonesia can produce 30-70 kg of fruit per tree in a single harvest per year, which is lower compared to Malaysia, Thailand, and India where yields can reach 200-300 kg of fruit per tree. The primary mangosteen production centers in Indonesia are located in West Java Province, specifically in Tasikmalaya, Subang, and Sukabumi. This research was conducted to identify the factors influencing mangosteen production. The research methodology employed a survey approach, collecting primary data directly from respondents (mangosteen farmers) and secondary data obtained from the Tasikmalaya District Central Statistics Agency. The study was conducted in Puspahiang Village, Puspahiang District, Tasikmalaya Regency, and simple random sampling was used for sample selection. The impact of production factors was analyzed using the Cobb-Douglas production function equation model. To assess the simultaneous effect, an F-test was conducted, and for the partial effects, a t-test was employed. The research findings indicate that variables such as land area, number of trees, organic fertilizers, labor force, and tree age collectively influence mangosteen production. Additionally, when examined individually, land area, number of trees, organic fertilizers, labor force, and tree age each have a significant impact on mangosteen production. The scale of production results suggests that a 1 percent increase in input will lead to a 2.216 percent increase in mangosteen production, indicating an increasing return scale.